The Effect of UMKM Growth in the Covid-19 Pandemic Period on Banda Aceh City's Economic Growth - Khairuna (Universitas Serambi Mekkah, 2021)
This study aims to determine the effect of UMKM growth on economic growth in Banda Aceh City. The aspects studied relate to variables such as the development of MSMEs that affect PDRB. The research data is seen from 2018-2020, this is to see a comparison of PDRB and an increase in the number of MSMEs, the Cooperatives service and the Aceh Province BPS. Data collection techniques in this study are interview and documentation techniques. The results of this study indicate that the acquisition of the coefficient of determination (R) indicates that UMKM growth is influenced by economic growth during the COVID-19 pandemic by 30.8% and the correlation coefficient (R2) indicates that MSME growth is influenced by economic growth in the UMKM sector during the pandemic. covid-19 by 95%. The results of the regression equation in this study were -5,487 for the UMKM variable. The results of the partial test show that the growth of MSMEs has an effect on economic growth.